1985
DOI: 10.1128/iai.47.2.446-451.1985
|View full text |Cite
|
Sign up to set email alerts
|

Relation of capsular materials and colony opacity to virulence of Vibrio vulnificus

Abstract: Colonies which varied in opacity were isolated from the four strains of Vibrio vulnificus. Opaque and translucent colonial types of the strains were distinguished from the corresponding parent strains. Variation in the opacity of colonies formed by each strain was accompanied by variation of capsular material formation, which was clarified by electron microscopy of the organisms stained with ruthenium red. The opaque-type colonies of the strains had capsular materials. On the other hand, three translucent-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(103 citation statements)
references
References 19 publications
6
95
0
2
Order By: Relevance
“…Therefore, it is assumed that Op and Tr variants of V. vulnificus may be phenotypes of the bacterium with or without the capsular material, respectively. Three of us have previously proved it by electron microscopy (25). The present serological and chemical studies also confirmed the hypothesis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, it is assumed that Op and Tr variants of V. vulnificus may be phenotypes of the bacterium with or without the capsular material, respectively. Three of us have previously proved it by electron microscopy (25). The present serological and chemical studies also confirmed the hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore the precipitin line of the PKF of Tr cells was not due to contamination of O antigen. Existence of a continuous thin layer of extracellular material on the Tr cells of L-180 which has been previously reported by three of us (25) was also demonstrated electron microscopically, although the layer was thinner than that of the isogenic Op-type variant (data not shown).…”
Section: Fig 2 Gel Diffusion Test Of K Antigen (Pkf) and O Antigen supporting
confidence: 73%
“…Amako et al (1984) reported the production of capsule by blood-isolated V. vulnificus 27562 and, therefore, only 17% of the cells were destroyed by serum. The capsule has the property of being resistant to serum and the phagocytic activity of polymorphonuclear cells, raising mice lethality (Yoshida et al 1985). Simpson et al (1987) found that, of 38 isolates of V. vulnificus, all virulent strains exhibited both opaque and translucent colonies when they were plated onto a variety of solid media.…”
Section: Table 4 Number (%) Of Virulent and Avirulent Vibrio Vulnificmentioning
confidence: 99%
“…After mice were injected i.v. with the bacteria (4.0 X 106 CFU), 0.05 ml of blood was obtained, at 1 min, 1, 3 and 5 h intervals, from the retroorbital plexus by capillary tubes as previously described [14]. After appropriate serial dilutions in PBS, viable cells in the blood were counted on CYE agar plates.…”
Section: Bacterial Clearance From the Bloodstream In Micementioning
confidence: 99%